A Comparative Study on Cyclic Behavior of S-Shaped and U-Shaped Steel Plate Dampers - Zhai, Zhipeng; Shu, Qi; Yao, Kaiying; Hu, Yao; Wang, Linfa (Salehan Institute of Higher Education, 2026)
The widely used U-shaped steel plate damper (USPD), featured by large deformation capacity and excellent energy dissipation efficiency, is incapable of achieving multi-level seismic control due to single-stage energy dissipation. To tackle this issue, a new S-shaped steel plate damper (SSPD) derived from USPD and sharing identical geometric dimensions is presented, which exploits a bending-tensile yield mechanism to form double-stage energy dissipation behavior. This paper carries out comprehensive numerical investigations with the aim of comparing the cyclic behavior of USPD and SSPD. Firstly, their configuration and working principle are elaborated, and an experimentally validated numerical modeling approach is proposed. Subsequently, numerical parametric analyses are conducted on models with various geometric dimensions. The performance of USPD and SSPD under cyclic loading is evaluated in terms of hysteresis characteristics, damage development, stiffness degradation, energy dissipation, and residual displacement, as well as their performances under low-cycle fatigue loading, which are analyzed. Finally, the calculation formulas for critical mechanical parameters of the dampers are recommended to facilitate the design in engineering practice. The results show that the ability of multi-level seismic control and superior cyclic performance support the application of SSPD in scenarios requiring the demand of multi-level seismic control and dual function of loading-bearing and energy-dissipating.